Inguinal plasty and appendectomy as treatment for Amyand's hernia: case report and literature review - Blaz Zavala, Rogelio A.; Uribe, Elizabeth Martinez; Flores Garcia, Alba E.; Calderon, Uriel Cruz; Elizondo, César Reyes (International Journal of Research in Medical Sciences, 2023)
Amyand's hernia is described as the presence of the caecal appendix within the hernial sac of an incarcerated inguinal hernia. It was reported as an incidental finding in 1% of cases and with evidence of appendicitis in 0.1% of cases. The approach involves performing appendectomy and inguinal repair in the same surgical time, depending on the clinical scenario and the surgeon's decisions. We presented the case of a 76-year-old male patient with a diagnosis of Amyand's right inguinal hernia diagnosed during trans-operative right inguinal plasty.